Stres Kerja, Komunikasi dan Lingkungan Kerja terhadap Kinerja Karyawan PT Indo Prima Nusantara - Cindy Cindy; Purnama Yanti Purba; Henry Christian Wijaya; Tommy Anggara (COSTING : Journal of Economic, Business and Accounting, 2020)
The business of making goods, the business of repairing goods, to the electronic and electrical credit businesses are found all around us. This study aims to determine and analyze the effect of work stress, communication, and work environment on employee performance. The phenomenon of increased public demand for electronic and electrical goods, increased work stress, ineffective communication, and an uncomfortable working environment underlie this research. The research method used is a quantitative approach, the type of research is quantitative descriptive, and the nature of this study is descriptive explanatory. The data analysis method used is multiple linear regression analysis. The sampling technique uses the saturation sampling method. The sample in this study was 80 employees. The results showed work stress, communication, and work environment had a positive and significant effect on employee performance. This means that the lower the work stress, the better the communication and work environment will be able to improve employee performance. Keywords: Job Stress, Communication, Work Environment, Employee Performance